Dynamic Plasma EGFR Mutation Status as a Predictor of EGFR-TKI Efficacy in Patients with EGFR-Mutant Lung Adenocarcinoma. Issue 4 (April 2015) - Tseng, Jeng-Sen; Yang, Tsung-Ying; Tsai, Chi-Ren; Chen, Kun-Chieh; Hsu, Kuo-Hsuan; Tsai, Meen-Hsin; Yu, Sung-Liang; Su, Kang-Yi; Chen, Jeremy J. W.; Chang, Gee-Chen
Abstract : Background: Epidermal growth factor receptor ( EGFR ) mutation status in lung cancer can effectively predict EGFR-tyrosine kinase inhibitor (TKI) efficacy. We evaluated the role of dynamic plasma cell-free DNA EGFR mutation status in outcome prediction. Methods: Advanced lung adenocarcinoma patients were enrolled and prospectively observed for outcomes of EGFR-TKI treatment. Peptide nucleic acid–zip nucleic acid polymerase chain reaction clamp method was developed to assess EGFR mutations in matched tumor and serial plasma cell-free DNA specimens. Results: A total of 72 patients were enrolled in this study, of which 62 patients (86.1%) had EGFR -mutant tumors (34 patients with exon 19 deletions, and 28 patients with L858R). Pretreatment plasma used for EGFR mutation testing showed a sensitivity of 59.7% and a specificity of 100%. Detection sensitivity was significantly higher in stage IV-M1b patients compared with stage IIIb and IV-M1a patients (78.0% versus 23.8%, p < 0.001). All patients who presented with EGFR -mutant tumors received first-line EGFR-TKI therapy. The objective response rate and disease control rate were 74.2% and 82.3%, respectively. Median progression-free survival and overall survival were 8.8 months (95% CI: 6.6–11.0) and 20.5 months (95% CI 15.1–26.0), respectively. Failure to clear plasma EGFR mutations after EGFR-TKI treatment was an independent predictor of lower disease control rate (odds ratio 5.26 [95% CI: 1.13–24.44]; p = 0.034), shorter progression-free survival (hazard ratio: 1.97 [95% CI: 1.33–2.91]; p = 0.001), and shorter overall survival (hazard ratio: 1.82 [95% CI: 1.04–3.18], p = 0.036). Conclusion: Changes in plasma EGFR mutation status can be successfully assessed using the peptide nucleic acid–zip nucleic acid polymerase chain reaction clamp method and can serve as an independent outcome predictor.